Mitigating a century of European renewable variability with transmission and informed siting - Jan Wohland; David Brayshaw; Stefan Pfenninger (Environmental Research Letters, 2021)
To reach its goal of net greenhouse gas neutrality by 2050, the European Union seeks to massively expand wind and solar power. Relying on weather-dependent power generation, however, poses substantial risks if climate variability is not adequately understood and accounted for in energy system design. Here we quantify European wind and solar generation variability over the last century, finding that both vary on a multidecadal scale, but wind more strongly. We identify hotspots and study dominant patterns of (co-)variability, finding that solar generation varies mostly uniformly across Europe while the leading wind variability modes reveal cross-border balancing potential. Combined wind and solar power generation in the current European system exhibits multidecadal variability of around 5% and can be further reduced through European cooperation or locally optimized wind shares, albeit the latter comes at the expense of significantly enhancing seasonal to interannual variability. Improved spatial planning therefore offers multiple options to mitigate long-term renewable generation variability but requires careful assessments of the trade-offs between climate-induced variations on different timescales.